PEMODELAN PELUANG KERUSAKAN MESIN MILLING CNC DI LABORATORIUM MESIN CNC MILLING POLITEKNIK NEGERI BENGKALIS UNTUK MENENTUKAN ESTIMASI BANYAKNYA JUMLAH KERUSAKAN DALAM RENTANG WAKTU TERTENTU DAN ESTIMASI BIAYA PERAWATAN DITINJAU DARI ASPEK AKTUARIA - Bustami Bustami; M.Alkadri Perdana (Politeknik Negeri Bengkalis, 2019)
To keep the CNC milling machine from being broken down quickly requires proper care and operation to extend the life of the machine. However, long-term machine break down, although not desirable, will be unavoidable. In this research we try to model the distribution of the engine breaking down probability by considering the first failure of the machine, which will be useful to predict the amount of machine failure in the future and also we model the cost of corrective maintenance. From the modeling results using several assumptions with the help of one of the statistical software obtained the rate of failure of CNC milling machine 55 mill which is in the laboratory of CNC machine is obtained weibul distributed from the modeling results and corrective maintenance cost of pareto which can be used in the prediction of the price of this machine's insurance premium.